Wykorzystanie funkcji dyskryminacyjnych do przewidywania upadku spółek giełdowych - Twardochleb, Barbara (The Usage of Discriminant Functions to Predict Bankruptcy of Companies on the Warsaw Stock Exchange, 2006)
This article presents the usage of multidimensional discriminant analysis (MDA) for the construction of linear discriminant functions W(X) and W"(X), which classify bankrupt and nonbancrupt companies on the Warsaw Stock Exchange for one and two years prior to failure. The empirical reaserch proved that only model W(X) can be used to predict financial distress of companies.The aim of the paper is to use a linear discrimination function in the capital market for the classification of the companies, based on financial ratios. The results of the classification were acceptable, investor can use the model W(X) for predicting bankruptcy and financial problems of the companies listed on the Warsaw Stock Exchange.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 120-129